2022
DOI: 10.3390/jcm11051436
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Computer-Aided Dynamic Navigation System in the Placement of Zygomatic Dental Implants: An In Vitro Study

Abstract: The objective of this in vitro study was to evaluate and compare the accuracy of zygomatic dental implant (ZI) placement carried out using a dynamic navigation system. Materials and Methods: Forty (40) ZIs were randomly distributed into one of two study groups: (A) ZI placement via a computer-aided dynamic navigation system (n = 20) (navigation implant (NI)); and (B) ZI placement using a conventional free-hand technique (n = 20) (free-hand implant (FHI)). A cone-beam computed tomography (CBCT) scan of the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In a cadaver study, a comparison between the modified surgical guide and the free-hand approach demonstrated a significant difference, which with the guide exhibited higher accuracy than the free-hand approach [ 10 ]. Another study compared the accuracy between the free-hand and navigation approach in 15 polyurethane models [ 47 ]. The results showed that the free-hand approach was more accurate than navigation in apical deviations.…”
Section: Discussionmentioning
confidence: 99%
“…In a cadaver study, a comparison between the modified surgical guide and the free-hand approach demonstrated a significant difference, which with the guide exhibited higher accuracy than the free-hand approach [ 10 ]. Another study compared the accuracy between the free-hand and navigation approach in 15 polyurethane models [ 47 ]. The results showed that the free-hand approach was more accurate than navigation in apical deviations.…”
Section: Discussionmentioning
confidence: 99%